Elaborasi Pesan Hoax Di Grup Facebook Info Wong Solo - Rahayu, Wien Hesthi; Utari, Prahastiwi (Komunikator, 2018)
Social media brings the new form of communication process, which appeared bad side of hoax messages dissemination. This study aims to find out how the media documents that include the contents of hoax messages, especially elaboration of hoax messages in the Facebook group INFO WONG SOLO with qualitative methods. This study shows, the Facebook group becomes the hoax information dissemination media. Unrecognised hoax informants are more likely to be found than informants with clear accounts. Hoax message informants tend to do political propaganda in the hoax message script. Strong argument types are used to support the informant's interests. So the audience need to recognize the characteristics of hoax messages and filtering of all information received.